2019
DOI: 10.1029/2018je005892
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oxidizing Aqueous Environments on Early Mars Inferred From Scavenging Pattern of Trace Metals on Manganese Oxides

Abstract: The Curiosity and Opportunity rovers have found depositions of manganese (Mn) (hydr)oxides within the veins of the sedimentary rocks at Gale and Endeavour craters. Since Mn is a redox sensitive element, revealing the chemical form of the Mn (hydr)oxide provides unique information on the redox state of the near‐surface/groundwater at the time of deposition. Here we report results of laboratory experiments that investigated scavenging patterns of trace metals (zinc, nickel, and chromium) on different Mn (hydr)ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Our observation of apatite within high-Mn material (Figures 4 and S8) would account for the increase in phosphorus observed in the Mn-rich nodule; and (g) Co-enrichments of Ni and Zn with Mn were observed by Curiosity and Opportunity rovers (Arvidson et al, 2016;Lanza et al, 2016). These observations and laboratory experiments (Noda et al, 2019) suggested that the high-Mn phases would be MnO 2 . By comparison, the Ni and Zn contents in the studied Mn-bearing material is below the detection limit of TEM-EDS technique.…”
Section: Discussionsupporting
confidence: 62%
“…Our observation of apatite within high-Mn material (Figures 4 and S8) would account for the increase in phosphorus observed in the Mn-rich nodule; and (g) Co-enrichments of Ni and Zn with Mn were observed by Curiosity and Opportunity rovers (Arvidson et al, 2016;Lanza et al, 2016). These observations and laboratory experiments (Noda et al, 2019) suggested that the high-Mn phases would be MnO 2 . By comparison, the Ni and Zn contents in the studied Mn-bearing material is below the detection limit of TEM-EDS technique.…”
Section: Discussionsupporting
confidence: 62%
“…Noda et al [15] conduct laboratory simulation experiments and elucidated that the ideal candidate of manganese oxides is x-MnO 2 (potential δ-MnO 2 ) excluding Mn 3 O 4 and Mn (OH) 2 , possibly resulting from the oxidization of reducing groundwater Mn 2+ with high-Eh (> 0.5 V) oxidants. [15] These observations indicated the presence and enrichment of Mn element on Mars, but the lack of accurately Mn-rich species results in obscure identification. Hence, accurately identifying manganese oxides is necessary to perform detailed laboratory synthesis of manganese oxides.…”
Section: Implications For Marsmentioning
confidence: 99%
“…On early Mars, atmospheric redox states may have dramatically varied over geological time (e.g., [11,58]). In Mars rover missions and Martian meteorite analyses, previous work focused on Mn; e.g., Mn (hydro)oxides, to reconstruct redox states of aqueous environments [3,4,7,10]. With microscopic analyses, ferrous saponite could be an alternative proxy indicator of oxidation on Mars.…”
Section: Mechanism Of Ferrous Saponite Oxidation and Its Implicationsmentioning
confidence: 99%
“…Knowledge of the redox evolution of aqueous environments on Mars is critical to understanding geochemical cycles and habitability (e.g., [1,2]). Sedimentary records revealed by Mars rovers, their interpretations based on experiments and modeling, and Martian meteorite analyses show that the redox states of aqueous environments would have dramatically changed on early Mars depending on time and locations (e.g., [3][4][5][6][7][8][9][10][11]).…”
Section: Introductionmentioning
confidence: 99%